Exploring Y-chromosomal STRs and SNPs for forensic and genetic insights in the Jiangsu Han population - Li, Min; Zhang, Han; Tao, Ruiyang; Chen, Anqi; Zhou, Peng; Yu, Chunjiang; Bian, Yingnan; Zhang, Suhua; Fang, Chen; Li, Chengtao (BMC genomics, 2025)
Y-chromosome short tandem repeats (Y-STRs) and single nucleotide polymorphisms (Y-SNPs) are valuable genetic markers used for individual identification, forensic applications, and the study of paternal lineage history. This study analyzed the genetic polymorphism and paternal genetic structure of the Han population in Jiangsu Province by examining 374 unrelated male individuals using 29 Y-STRs and 183 Y-SNPs. Forensic parameters were calculated, and the discriminatory power of five Y-STR systems (MHT, EXT, PPY12, Yfiler, and Y29) was compared. Genetic structure was assessed in the context of the Jiangsu Han and other Chinese populations. Results showed that the Y29 system had the highest discriminatory capacity, identifying 374 unique haplotypes with HD and DC values of 1. Seven major haplogroups (C, D, J, K, O, Q, R) and 83 terminal haplogroups were identified, with haplogroup O being the most predominant (approximately 85%). Subdivision of haplogroup O revealed that the Jiangsu Han population exhibits genetic characteristics of both Southern and Northern Han groups. Population genetic analyses further confirmed that the Jiangsu Han clustered closely with Southern Han populations. Genetic admixture results revealed that the Jiangsu Han population derives 89% of their ancestry from Southern Han populations, while retaining 11% Northern Han contributions. The study provides valuable insights into the genetic structure of the Jiangsu Han population, with significant implications for forensic genetics, anthropological research, and broader population genetics studies.